The Hard Ferromagnetism in FePS3 Induced by Non‐Magnetic Molecular Intercalation - Ou, Yunbo; Li, Xiaoyin; Kopaczek, Jan; Davis, Austin; Jackson, Gigi; Sayyad, Mohammed; Liu, Feng; Tongay, Seth Ariel (Advanced Physics Research, 2025)
Manipulating the magnetic ground states of 2D magnets is a focal point of recent research efforts. Various methods have demonstrated efficacy in modulating the magnetic properties inherent to van der Waals (vdW) magnetic systems. Herein, the emergence of robust anisotropic ferromagnetism within antiferromagnetic FePS3 is unveiled via intercalation with non‐magnetic pyridinium ions. A one‐step ion exchange reaction facilitates the formation of energetically favorable B‐phase and metastable P‐phase. Notably, both B‐ and P‐phases manifest hard ferromagnetic behavior, featuring substantial unsaturated coercive fields (>7 T) and high Curie temperatures (72–87 K). First‐principles calculations elucidate the pivotal role of electron transfer from pyridinium ions to FePS3 in engineering magnetic exchange interactions. Calculated effective spin Hamiltonian corroborates the observed hard ferromagnetism in intercalated FePS3. This study offers crucial insights into hard magnetism in intercalated vdW materials, thereby presenting promising avenues for 2D vdW magnet‐based magnetic devices. This study reveals the emergence of robust anisotropic ferromagnetism in antiferromagnetic FePS₃ via intercalation with non‐magnetic pyridinium ions. Both B‐ and P‐phases exhibit hard ferromagnetic behavior with high coercive fields (>7 T) and Curie temperatures (72–87 K). First‐principles calculations demonstrate how electron transfer modulates magnetic exchange interactions, offering insights into 2D van der Waals magnetic materials.